Clinical Outcome of Direct Pulp Therapy in Primary Teeth: A Systematic Review and Meta-analysis - Parimala Kulkarni; Shilpi Tiwari; Nikita Agrawal; Anup Kumar; Poorva Umarekar; Sanjana Bhargava (Wolters Kluwer Medknow Publications, 2022)
Background: Direct pulp treatment is carried out when a healthy pulp gets mechanically/accidentally exposed during the operative procedures or trauma. Aim: To determine the effects of various direct pulp capping materials as measured by the clinical and radiographic analysis. Design: Two reviewers performed a database search of the studies published between January 2005 and November 2020. The inclusion criteria were papers published in the English language; children aged 3-12 years having deep carious lesions in primary teeth. All potential studies were acknowledged by their title and abstract. The full-text analysis of potentially relevant studies, the selected studies were included in the systematic review. A meta-analysis calculation was performed for the overall data and the subgroup data. Results: The database searching led to 57 articles, which were of direct pulp treatment in primary teeth, after the removal of duplicates, 55 records remained but did not meet all inclusion criteria. A high variability was observed among the papers. Further filtering with criteria led to nine articles, which met all inclusion criteria. Meta-analysis demonstrated the success rates of DPT in primary teeth (95% confidence interval −0.799-0.898); P < 0.001. Clinical assessments of various direct pulp capping materials suggested 84.9% of success irrespective of the material used. The nine studies were heterogeneous according to the random effect model (P < 0.001, I2 = 84.08%). Conclusions: Direct pulp treatment has the advantage of being a conservative vital pulp therapy reducing the need for a more invasive treatment.